Kemampuan Fusan F1 Dalam Memproduksi Inulinase - Wijanarka, Wijanarka; Soetarto, Endang Sutariningsih; Dewi, Kumala; Indrianto, Ari (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Fusan F1 was the result of the fusion of the Pichia manshurica and Rhodosporidium paludigenum. The second type of yeast has the ability to produce inulinase.Â Inulinase (EC. 3.2.1.7) is an enzyme that is classified as a hydrolase enzyme, this enzyme has the ability to break down complex inulin into simpler components that fructose. Fructose was a monosaccharide with huge potential for the manufacture of butanol, iOS, pullan, FOS and ethanol. The purpose of research to determine the ability fusan F1 in producing inulinase and to determine the specific growth rate (Î¼), as well as the generation time (g) fusan F1.The results showed that fusan F1 at the 18 thhour was able to produce inulinase of 0.61 mol / min. These results are higher than the parental namely P. manshurica (0.56 mol / min) and Rh. paludigenum (0.33 mol / min). While The specific growth rate (Î¼) and generation time (g) fusan F1 respecly 0.25 h and 2.7/ h. Keywords: Fusan F1; inulinase; the specific growth; generation time